Some reflections about challenges of education policies in the Colombian Caribbean: a media analysis (Papeles, 2018)
The article presents the results of a content analysis of news pieces about education published in two main periodicals from northern Colombia. El Heraldo is a newspaper that targets, mainly, opinion leaders from cities like Barranquilla, while the audience of the Diario La Libertad concentrates, widely, in popular classes and inhabitants from municipalities in the region. The exercise of contrasting themes and debates disseminated in both sources reveals the complexities behind education policy processes that emerged from events such as the expedition of Law 715 of 2001. The findings from this study highlight some methodological considerations that invite researchers and politicians to innovate in debates regarding the educational challenges of the country.
Keywords: education policy; media analysis; quality of education; research methodology